The Quality of Video Games: Subjective Quality Assessments as Predictors of Self-Reported Presence in First-Person Shooter and Role-Playing Games. Issue 4 (1st October 2016) - Schumann, Christina; Bowman, Nicholas David; Schultheiss, Daniel
Abstract : Based on the Theory of Subjective Quality Assessments, the present study examined players' assessments of video game design features (qualities) as related to self-reported feelings of presence in role-playing games (RPG) and first-person shooters (FPS). An initial qualitative study with 8 focus groups (Study 1) was conducted to explore important game quality dimensions. Afterwards an online survey was designed to explore the association of those discrete dimensions with recollections of presence (Study 2). Using a quota sample of RPG and FPS gamers in Germany (N = 5, 180), survey results show that recollections of presence were associated with positive quality assessments regarding a game's environment, the player's interaction with non-playable characters in that environment, and the environment's.